Minimum Wages, Wage Dispersion and Financial Constraints in Firms - Hamzeh Arabzadeh; Almut Balleer; Britta Gehrke; Ahmet Ali Taskin (Institute of Labor Economics (IZA), 2023)
This paper studies how minimum wages affect the wage distribution if firms face financial constraints. Using German employer-employee data and firm balance sheets, we document that the within-firm wage dispersion decreases more with higher minimum wages when firms are financially constrained. We introduce financial frictions into a search and matching labor market model with stochastic job matching, imperfect information, and endogenous effort. In line with the empirical literature, the model predicts that a higher minimum wage reduces hirings and separations. Firms become more selective such that their employment and wage dispersion fall. If effort increases strongly, firms may increase employment at the expense of higher wage dispersion. Financially constrained firms are more selective and reward effort less. As a result, within-firm wage dispersion and employment in these firms fall more with the minimum wage.
Keywords: J31; J38; J63; J64; 330; minimum wage; wage dispersion; financial frictions; search and matching; unemployment